2021
DOI: 10.1093/jjco/hyaa245
|View full text |Cite
|
Sign up to set email alerts
|

Rapid on-site evaluation of touch imprints of biopsies improves the diagnostic yield of transbronchial biopsy for endoscopically nonvisible malignancy: a retrospective study

Abstract: Objective Rapid on-site evaluation has long been used for transbronchial needle aspiration or fine-needle aspiration to evaluate the adequacy of biopsy materials for the diagnosis of peripheral lung lesions. However, research on rapid on-site evaluation combined with transbronchial forceps biopsy in the diagnosis of lung carcinoma is rarely reported. Therefore, we aimed to investigate the value of rapid on-site evaluation during transbronchial forceps biopsy for endoscopically visible (tumor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The ROSE result was consistent with the histopathological results for pulmonary cancer and peripheral pulmonary lesion doagnosis. 8 , 17 , 18 A high coincidence rate between ROSE and histopathological findings, with a kappa value of 0.574, was also observed; the positive diagnostic rate of PC did not change significantly. Therefore, ROSE has good consistency with histopathology for PC diagnosis and exhibits a certain level of accuracy and timeliness.…”
Section: Discussionmentioning
confidence: 68%
“…The ROSE result was consistent with the histopathological results for pulmonary cancer and peripheral pulmonary lesion doagnosis. 8 , 17 , 18 A high coincidence rate between ROSE and histopathological findings, with a kappa value of 0.574, was also observed; the positive diagnostic rate of PC did not change significantly. Therefore, ROSE has good consistency with histopathology for PC diagnosis and exhibits a certain level of accuracy and timeliness.…”
Section: Discussionmentioning
confidence: 68%
“…Rapid on-site evaluation (ROSE) is used to con rm tumor cells in cytological specimens, and its utility in bronchoscopy has been studied using endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), which suggested that ROSE improves the diagnostic yield of EBUS-TBNA and decreases the number of biopsies required [20][21][22]. The same has been reported for bronchoscopy of PPL [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 98%
“…When performing ROSE during bronchoscopy using EBUS-GS for PPL, two types of cytology specimens must be evaluated: imprint cytology of forceps biopsy and brush cytology. There are many reports on ROSE of imprint cytology of forceps biopsy [23][24][25][26], but there are few reports on brush cytology [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid on-site evaluation (ROSE) is a cytomorphological diagnostic procedure that assesses the adequacy and accuracy of the material obtained during bronchoscopy within a few minutes in or near the bronchoscopy suite (on-site) using rapid staining (e.g., Diff-Quik or Hemacolor) of touch imprints of biopsies (5). ROSE has been reported to improve the diagnostic yield of transbronchial biopsy for endoscopically non-visible malignancy during transbronchial forceps biopsy (TFB) (6), to obtain high diagnostic performance and an acceptable rate of complications during computed tomography (CT)-guided fine-needle aspiration (FNA) for pulmonary lesions (7,8), to significantly improve diagnostic yields (9), and to lower the additional number of biopsies (10)(11)(12) during transbronchial needle aspiration (TBNA).…”
Section: Introductionmentioning
confidence: 99%